The Bridge Motif And Reflexive Thinking. Of The Necessity Of Thoughtfulness In Vukelich’s Der Mann auf der Brücke - Jug, Stephanie (Anafora, 2024)
Wilma Vukelich’s Manuscript Der Mann auf der Brucke was composed in 1955 in Zagreb, one year prior to the death of this German writing author. The title bridge motif is analyzed as a literary motif and a metaphor for reflexive thinking. This reading offers valuable insights into literature, culture and philosophy of the 20th century by showing that thoughtfulness or consideration are highlighted both as endangered structures of thought and as essential for humanity as such. The problem can be identified already in classical works, e. g. in the Faust narrative, but gets a specific expression in the political and social turmoil of the 20th century. The basis for this reading, laid by Clayton Koelb’s interpretation of Franz Kafka’s parabola The Bridge, is broadened and applied to Vukelich’s novel in manuscript form. The analyzed manuscript is read against Vukelich’s life and her other works and the bridge motif investigated in all its facets. Ultimately the interpretation points towards Hannah Arendt’s concept of the truth which lies in limbo, which can be taken as a philosophical and practical application of the here discussed bridge concept.